Singapore botanic gardens (SBG) : total economic value and opportunity cost of conserving SBG - Ang, Kheng Li (2016)
What is the Total Economic Value (TEV) of Singapore Botanic Gardens (SBG)? How does this value compare to the opportunity cost of the land price? In this study, contingent valuation method is carried out using survey questionnaires to elicit willingness to pay (WTP) of respondents. In addition, direct market valuation determines the marketable component of SBG such as direct use value (orchids) and indirect use value (carbon storage of trees). The WTP is further allocated to four non-marketable values consisting of recreational value, option value, existence value and bequest value. The relative importance of the four non-marketable values allows us to gain insights on the public valuation of each value with respect to SBG. Our main findings could be summed up as follows: (1) The opportunity cost is higher than the TEV of SBG. The public do not understand the true value of SBG. (2) Greenery, Garden Quality, Gender, Frequency and Income have a significant correlation with WTP and (3) Bequest and recreational value is of higher importance to an individual compared to option and existence value.